1977
DOI: 10.1136/pgmj.53.617.146
|View full text |Cite
|
Sign up to set email alerts
|

Primary anorexia nervosa (weight phobia) in males

Abstract: Summary Ten cases of primary anorexia nervosa (weight phobia) in males (as against 196 females) have been treated in the United Birmingham Hospitals over 19 years. A discrete syndromes appears to exist with much to support the view that it is the counterpart of primary anorexia nervosa in the female. Six illustrative case histories are described briefly. The heavy loading with consistent abnormalities of psychiatric interest makes it very probable that weight phobia is primarily a psychiatric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Suicidal features, such as reported by Hasan and Tibbetts [23] and Fichter et al 1161 were also evident in the present study. Suicidal ideation was noted in 45% of our patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Suicidal features, such as reported by Hasan and Tibbetts [23] and Fichter et al 1161 were also evident in the present study. Suicidal ideation was noted in 45% of our patients.…”
Section: Discussionsupporting
confidence: 80%
“…This was not supported in the present study where there was a trend towards being the second or third child (Table I), as has been found in several other studies [ 15,231. Eating disorders rarely have been reported in the siblings of patients with anorexia and bulimia nervosa [23] as was the case in the present study. reported a BMI of only 12.9 whereas Hall er a1 (251 one of 20.5.…”
Section: Discussionmentioning
confidence: 42%
“…In addition, symptomatic epilepsy, due to such metabolic disturbances, was a feature of at least one case and was described as reminiscent of similar findings in the female population (Crisp et al, 1968). Hasan and Tibbetts (1977) found an interest in providing food for others to be common, and 3 of their 10 young men had expressed a wish to become chefs or to take up catering as a career. Restlessness and overactivity were noted, and affective disturbance was common.…”
Section: Other Studiesmentioning
confidence: 97%
“…Crisp and Toms (1972) felt the reported homosexual conflicts were analogous to the heterosexual threat in the female. Hasan and Tibbetts (1977) saw homosexual conflicts in their patients as well as a noticeable lack of assertive masculinity or identification. Weiner (1976) reported that the father of an anorexic patient openly expressed his fears regarding his son's homosexual tendencies.…”
Section: Sex Differentialmentioning
confidence: 99%